2013
DOI: 10.4081/or.2013.e27
|View full text |Cite
|
Sign up to set email alerts
|

Massive hematothorax after thoracic spinal manipulation for acute thoracolumbar pain

Abstract: Spinal manipulation usually represents a widely used and effective method for physicians in order to relieve acute patient pain and muscular dysbalance. Although life-threatening complications (e.g. pneumothorax, vertebral artery dissection, stroke) after manual treatment are reported with regard to actual medical literature millions of patients undergo manual treatment to manage thoracolumbar pain each year. The authors present the case of a 17 year old male patient with a life-threatening hematothorax after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Adverse events were defined as mild (transient effects lasting b 24 hours, eg, crying or discomfort), moderate (requiring medical/general practitioner treatment), or severe (requiring hospital treatment) 16 39 Wilson et al, 41 Zimmerman et al, 52 Humphreys, 21 Alcantara et al, 25,[35][36][37][38] Posadzki and Ernst, 24 Simonian and Staheli, 43 53 Ziv et al, 54 Jacobi et al, 46 L'Ecuyer, 55 Klougart et al, 51 Rageot, 47 40 Miller and Benfield, 26 Doyle, 44 Holla et al, 42 Hayes and Bezilla, 27 Hayden et al, 28 Dobson et al, 22 Pohlman and Holton-Brown, 23 Sawyer et al, 29 Koch et al, 30,31 Bronfort et al, 34 Philippi et al, 32 Rowe et al 33 Manual search of reference lists revealed additional 6 articles: Wiberg et al, 59 Straub et al, 60 Sandell et al, 61 Balon and Aker, 62 Khorshid et al, 63 …”
mentioning
confidence: 99%
“…Adverse events were defined as mild (transient effects lasting b 24 hours, eg, crying or discomfort), moderate (requiring medical/general practitioner treatment), or severe (requiring hospital treatment) 16 39 Wilson et al, 41 Zimmerman et al, 52 Humphreys, 21 Alcantara et al, 25,[35][36][37][38] Posadzki and Ernst, 24 Simonian and Staheli, 43 53 Ziv et al, 54 Jacobi et al, 46 L'Ecuyer, 55 Klougart et al, 51 Rageot, 47 40 Miller and Benfield, 26 Doyle, 44 Holla et al, 42 Hayes and Bezilla, 27 Hayden et al, 28 Dobson et al, 22 Pohlman and Holton-Brown, 23 Sawyer et al, 29 Koch et al, 30,31 Bronfort et al, 34 Philippi et al, 32 Rowe et al 33 Manual search of reference lists revealed additional 6 articles: Wiberg et al, 59 Straub et al, 60 Sandell et al, 61 Balon and Aker, 62 Khorshid et al, 63 …”
mentioning
confidence: 99%
“…One must remember that acupuncture and chiropractice are the most studied CAM therapies with many control studies that have also reported side effects. Even so, when searching PubMed, one can find more than 1,800 articles about chiropractic manipulation, but only three discuss the dangers in these manipulations 2022. Some leading Israeli hospitals include CAM in their services, mainly in pain clinics.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 10 cases, reported in seven articles, were analysed for this systematic review [33][34][35][36][37][38][39] (Table 3).…”
Section: Demographicsmentioning
confidence: 99%